Color-Shift Keying for Optical Camera Communication Using a Rolling Shutter Mode - Hao-Wei Chen; Shang-Sheng Wen; Xing-Lin Wang; Ming-Zhu Liang; Mu-Yun Li; Qing-Chang Li; Yun Liu (IEEE Photonics Journal, 2019)
An optical camera communication (OCC) is a special type of a visible light communication that uses a complementary metal-oxide semiconductor as a receiver. However, it is difficult to apply a high-order modulation scheme to such communications because of strong intersymbol interference. In this paper, we propose and demonstrate an OCC system using an 8-color color-shift keying scheme. We used an RGB-based LED light panel as a transmitter and analyzed the properties of the rolling shutter. We discuss the demodulation process and perform bit error rate (BER) tests at different ambient illuminances and sampling positions. A net data rate of 8.64 kbps and a pixel efficiency of 3.75 pixels per bit were achieved while keeping the BER below 3.8E-3, which meets the FEC's 7% forward error correction requirement. In addition, the system shows good robustness for indoor applications.